2009
DOI: 10.1016/j.bbamcr.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal involvement in cell death and cancer

Abstract: Lysosomes, with their arsenal of degradative enzymes are increasingly becoming an area of interest in the field of oncology. The changes induced in this compartment upon transformation are numerous and whereas most are viewed as pro-oncogenic the same processes also render cancer cells susceptible to lysosomal death pathways. This review will provide an overview of the pro- and anti-oncogenic potential of this compartment and how these might be exploited for cancer therapy, with special focus on lysosomal deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
280
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(288 citation statements)
references
References 122 publications
6
280
0
2
Order By: Relevance
“…Importantly, transformation is associated with an increase in the volume and activity of the lysosomal compartment and even highly apoptosis-resistant cancer cells are frequently prone to cell death pathways mediated by lysosomal cathepsins (36,37). The data presented above add BAMLET to the growing list of cytotoxic agents that can induce a nonapoptotic lysosomal cell death pathway (35). In light of these data, combination therapies with agents further sensitizing cells to lysosomal destabilization (such as microtubule disturbing drugs vincristine and paclitaxel) as well as with those inducing lysosomal destabilization (such as siramesine) should be experimentally tested (38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, transformation is associated with an increase in the volume and activity of the lysosomal compartment and even highly apoptosis-resistant cancer cells are frequently prone to cell death pathways mediated by lysosomal cathepsins (36,37). The data presented above add BAMLET to the growing list of cytotoxic agents that can induce a nonapoptotic lysosomal cell death pathway (35). In light of these data, combination therapies with agents further sensitizing cells to lysosomal destabilization (such as microtubule disturbing drugs vincristine and paclitaxel) as well as with those inducing lysosomal destabilization (such as siramesine) should be experimentally tested (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Among them are the lysosomes with their large arsenal of proteolytic and lipolytic hydrolases (4,34,35). Importantly, transformation is associated with an increase in the volume and activity of the lysosomal compartment and even highly apoptosis-resistant cancer cells are frequently prone to cell death pathways mediated by lysosomal cathepsins (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Besides being tagged for ubiquitin mediated degradation by c-Cbl, the ligand activated EGFR molecules are also degraded by lysosomal proteases, which is mediated via clathrin-coated pits involving endosomal pathway. Mutations and expression anomalies of genes regulating both proteasome and lysosomal degradation pathways have been reported in several carcinomas (Kirkegaard et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The resistance induced by LAMP3 is primarily directed towards proteasome inhibitors used during chemotherapy. In conclusion, it has been found that increased expression of LAMP3 contributes to the development of autophagy and cell survival [6] [27]. It is important when developing new therapies, including molecularly targeted therapies, to inhibit the specific cytokine activating the signaling pathway involved in a particular disease.…”
Section: Discussionmentioning
confidence: 99%